Novel Role for Cardiolipin as a Target of Therapy to Mitigate Myocardial Injury Caused by Venoarterial Extracorporeal Membrane Oxygenation - Swain, Lija; Bhave, Shreyas; Qiao, Xiaoying; Reyelt, Lara; Everett, Kay D.; Awata, Junya; Raghav, Rahul; Powers, Sarah N.; Sunagawa, Genya; Natov, Peter S.; Mahmoudi, Elena; Warner, Mary; et al. (Circulation (New York, N.Y.), 2024)
BACKGROUND: Cardiolipin is a mitochondrial-specific phospholipid that maintains integrity of the electron transport chain (ETC) and plays a central role in myocardial ischemia/reperfusion injury. Tafazzin is an enzyme that is required for cardiolipin maturation. Venoarterial extracorporeal membrane oxygenation (VA-ECMO) use to provide hemodynamic support for acute myocardial infarction has grown exponentially, is associated with poor outcomes, and is under active clinical investigation, yet the mechanistic effect of VA-ECMO on myocardial damage in acute myocardial infarction remains poorly understood. We hypothesized that VA-ECMO acutely depletes myocardial cardiolipin and exacerbates myocardial injury in acute myocardial infarction. METHODS: We examined cardiolipin and tafazzin levels in human subjects with heart failure and healthy swine exposed to VA-ECMO and used a swine model of closed-chest myocardial ischemia/reperfusion injury to evaluate the effect of VA-ECMO on cardiolipin expression, myocardial injury, and mitochondrial function. RESULTS: Cardiolipin and tafazzin levels are significantly reduced in the left ventricles of individuals requiring VA-ECMO compared with individuals without VA-ECMO before heart transplantation. Six hours of exposure to VA-ECMO also decreased left ventricular levels of cardiolipin and tafazzin in healthy swine compared with sham controls. To explore whether cardiolipin depletion by VA-ECMO increases infarct size, we performed left anterior descending artery occlusion for a total of 120 minutes followed by 180 minutes of reperfusion in adult swine in the presence and absence of MTP-131, an amphipathic molecule that interacts with cardiolipin to stabilize the inner mitochondrial membrane. Compared with reperfusion alone, VA-ECMO activation beginning after 90 minutes of left anterior descending artery occlusion increased infarct size (36±8% versus 48±7%; P<0.001). VA-ECMO also decreased cardiolipin and tafazzin levels, disrupted mitochondrial integrity, reduced electron transport chain function, and promoted oxidative stress. Compared with reperfusion alone or VA-ECMO before reperfusion, delivery of MTP-131 before VA-ECMO activation reduced infarct size (22±8%; P=0.03 versus reperfusion alone and P<0.001 versus VA-ECMO alone). MTP-131 restored cardiolipin and tafazzin levels, stabilized mitochondrial function, and reduced oxidative stress in the left ventricle. CONCLUSIONS: We identified a novel mechanism by which VA-ECMO promotes myocardial injury and further identify cardiolipin as an important target of therapy to reduce infarct size and to preserve mitochondrial function in the setting of VA-ECMO for acute myocardial infarction.